A 16-week school-based intervention improves physical fitness in Slovenian children: a randomized controlled trial - Petrušič, Tanja; Novak, Dario (Frontiers in Physiology, 2024)
The aim of this study was to evaluate the impact of a 16-week school-based physical activity (PA) intervention on the physical fitness (PF) of 8-9-year-old children. Seventy-eight students (45 boys: age 8.4 ± 4.9 years; 42 girls: age 8.6 ± 0.5 years) from a Slovenian school were randomly assigned to either an experimental group (EXP), which participated in an extracurricular PA program, or a control group (CON), which participated only in mandatory physical education (PE). The EXP group's program, which took place twice a week for 60 minutes for 16 weeks, included elementary PE games with elements of athletics (e.g., skipping, push-off running, hopping, cross-stepping, and jumping) and gymnastics (e.g., handstand, forward roll, backward roll, hand support jumps, squat jump on a vault box, climbing on horizontal bars, incline benches and ropes, crawling and jumping rope) designed to improve speed, hand-eye coordination and flexibility. PF was assessed using standardized tests: sit and reach test (SAR), 30-meter sprint, and the alternate handwall toss test at 1.0 and 2.0 meters (AHWT 1.0 and 2.0). Significant improvements were observed in the EXP group for SAR (increase of 1.6 cm, 6.3%), 30-meter sprint (decrease of 0.4 seconds, 6.3%) and AHWT 1.0 (increase of 2.1 points, 25.6%). The CON group showed minimal or no changes. For the AHWT 2.0 meter, no significant difference was observed for either group. Post-hoc tests revealed significant progress in the EXP group for SAR, 30-meter sprint and AHWT 1.0, while the CON group showed no significant changes in these tests or the AHWT 2.0. The results show that the extracurricular PA program significantly improved PF components in 8- to 9-year-olds with only two additional sessions per week. The most notable improvements were in flexibility, speed and coordination, as seen in the SAR tests, the 30-meter sprint and the 1.0-meter handwall toss tests. However, there was no comparable progress in the 2.0-meter hand wall toss. This highlights the specific areas impacted by the PA program and demonstrates its effectiveness in improving key PF components in young children.